Recovery of stereoacuity after Yokoyama procedure in patients with highly myopic strabismus with good vision - Tamami Shimizu; Akiko Hikoya; Miwa Komori; Hiroko Suzuki; Yoshihiro Hotta; Miho Sato (American Journal of Ophthalmology Case Reports, 2023)
Purpose: To report stereopsis after bilateral Yokoyama procedure in patients with highly myopic strabismus and good visual acuity. Observations: Five patients aged between 34 and 81 years with best-corrected visual acuity of 20/25 or better were operated on. The preoperative strabismus angle ranged from esotropia of 35–113 prism diopters (PD) at distance and esotropia of 40–113 PD at near. One patient had left hypotropia of 4 PD and excyclotorsion of 15°, and the other had left hypotropia of 10 PD. Their axial lengths were 27.65–33.07 mm, and the posterior globe dislocation angles were between 123 and 148° on coronal magnetic resonance imaging (MRI). Limitations of abduction were between −1 and −2. All patients complained of diplopia, and none of them showed stereopsis. The Yokoyama procedure was performed on both eyes. Postoperative alternate cover testing showed from esotropia of 2 PD to exophoria of 8 PD at distance and from exotropia of 12 PD to esophoria of 10 PD at near.Three patients recovered stereopsis of 100, 50, and 140 sec, respectively. Two cases required unilateral inferior rectus muscle recessions, and their postoperative stereopsis was 25 and 50 sec. Conclusions and Importance: The Yokoyama procedure is effective not only in cases of heavy eye syndrome but also in cases of myopic esotropia associated with a globe dislocation angle of 120° or with little abduction restriction. If visual acuity is good, stereopsis may be restored with improvement in eye deviation.